Liberation eaudiobook - Brown, Ryk (Frontiers Saga, 2014)
Heartfelt reunions with friends...Desperate plans to gain advantage...Opportunities that cannot be ignored...Discovery of family once thought lost... The time has come for Captain Scott to fight for that which was taken...the very freedom of the world he was sworn to protect.